Oil and property rights - Indra de Soysa; Tim Krieger; Daniel Meierrieks (Resources Policy, 2022)
We investigate the role of oil in economic institutions for a sample of 150 countries between 1960 and 2014. We find that higher per capita values of oil production result in weaker economic institutions in the form of lower levels of private property rights protection. This result is robust to alternative instrumental-variable approaches as well as different operationalizations of oil income and production as well as economic institutions. We argue that our finding is indicative of oil interest groups using their economic power to achieve weaker property rights to maintain their economic-political position in society. We also provide evidence that oil induces clientelism, corruption and the repression of dissenting political voices. We argue that this finding is consistent with the idea that oil interest groups translate their outsized economic into political power through these transmission channels to achieve lower levels of property rights protection.
Keywords: 330; oil; oil production; economic institutions; property rights; institutional resource curse